2017
DOI: 10.1051/limn/2016040
|View full text |Cite
|
Sign up to set email alerts
|

Spatial heterogeneity and seasonal succession of phytoplankton functional groups along the vertical gradient in a mesotrophic reservoir

Abstract: -Tracking morphological variability of phytoplankton is a useful tool to better understand environmental changes. Highly dynamic systems such as reservoirs are convenient environments to investigate the effects of environmental variables on phytoplankton morphology. However, to fully understand the effects of mixing and trophic state on phytoplankton functional group (FG) distribution, the entire water column must be considered since integrated or sub-superficially collected samples, may not adequately represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 53 publications
2
6
0
1
Order By: Relevance
“…During the present study, Bacillariophyta was the most dominant group in the phytoplankton composition. Dominancy of this group in phytoplankton community is also agreement with previous studies in Valparáiso Reservoir (Negro et al 2000), El Gergal Reservoir (Hoyer et al 2009) Spain, Marathonas Reservoir (Greece) (Katsiapi et al 2011), Paraja limno-Reservoir in Spain (Molina-Navarro et al 2014) and in Alleben Reservoir by Çelekli and Öztürk (2014) and İkizcetepeler Reservoir by Sevindik et al (2017) in Turkey.…”
Section: Phytoplankton Composition and Their Environmental Relationshipssupporting
confidence: 91%
See 1 more Smart Citation
“…During the present study, Bacillariophyta was the most dominant group in the phytoplankton composition. Dominancy of this group in phytoplankton community is also agreement with previous studies in Valparáiso Reservoir (Negro et al 2000), El Gergal Reservoir (Hoyer et al 2009) Spain, Marathonas Reservoir (Greece) (Katsiapi et al 2011), Paraja limno-Reservoir in Spain (Molina-Navarro et al 2014) and in Alleben Reservoir by Çelekli and Öztürk (2014) and İkizcetepeler Reservoir by Sevindik et al (2017) in Turkey.…”
Section: Phytoplankton Composition and Their Environmental Relationshipssupporting
confidence: 91%
“…The reservoirs showed alkaline water with pH ranged from 8.7 to 8.8. These pH values were higher than the mean pH value found at Alleben Reservoir (Çelekli and Öztürk, 2014) and similar to those found at İkizcetepeler Reservoir by Sevindik et al (2017) in Turkey. The highest conductivity (434.5 µS cm -1 ) and salinity (0.21 ppt) were measured at Sevişler Reservoir.…”
Section: Physical and Chemical Parameterssupporting
confidence: 67%
“…The codon L O , which is known to regulate its buoyancy and tolerate low nutrient concentrations (Petar et al, 2014), showed a negative correlation with NO 2 + NO 3 (r = -0.621; P < 0.05) and TP (r = -588; P < 0.05) in the lake. Similarly, Sevindik et al (2017) detected the codon L O and F in the mesotrophic İkizcetepeler reservoir during the summer period.…”
Section: Pfgs and Their Ecological Preferencesmentioning
confidence: 84%
“…Few studies had also been conducted to use PFGs in determination of the water quality of Turkish reservoirs and lakes in recent years (Soylu and Gönülol, 2010;Çelekli and Öztürk, 2014;Demir et al, 2014;Maraşlıoğlu and Gönülol, 2014;Çelik and Sevindik, 2015;Sevindik et al, 2017;Varol, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This analysis employed the integrated water column, which was collected using a plastic tube 2 cm in diameter (INAG 2009;Navarro et al 2006;Becker et al 2010). The integrated water column represented the depth of the photic zone, which was determined by multiplying the Secchi disk depth by 2.7 (Cole 1994;Huszar et al 2000;Soares et al 2008;Sevindik et al 2017). Previous studies have linked the eutrophication of some of the studied reservoirs (Mariani and Pompêo 2008) to metals contamination, and the TSI is an important tool for evaluation of the allochthonous contribution of possible contaminants in the aquatic ecosystem.…”
Section: Measurement Of Other Sediment Parametersmentioning
confidence: 99%